Boosting hydrogen evolution through hydrogen spillover promoted by Co-based support effect. Issue 13 (8th March 2023) - Zhou, Ya-Nan; Liu, Xin; Yu, Cheng-Jie; Dong, Bin; Han, Guan-Qun; Liu, Hai-Jun; Lv, Ren-Qing; Liu, Bin; Chai, Yong-Ming
Abstract : The degree of hydrogen spillover of Pt loaded-samples increased in the sequence of selenides < sulfides < oxides < phosphides, which is contrary to the trend of work function difference between Pt and supports, thus enhancing HER activity in this order. Abstract : Hydrogen spillover as an effective strategy can be used to elevate electrocatalytic activity for the hydrogen evolution reaction (HER). However, the extent and efficiency of hydrogen spillover on different kinds of supports remains a puzzle, limiting the design of high-activity catalysts. Herein, we have prepared a series of samples loaded with Pt and made close supervision of hydrogen spillover behavior. Experimental and theoretical simulations show that the degree of hydrogen spillover increased in the sequence of selenides < sulfides < oxides < phosphides, which is contrary to the trend of work function difference between Pt and supports (Δ Φ ), thus enhancing HER activity in this order. With low Pt loading, the smooth Pt-to-support migration of hydrogen intermediates, thanks to the electron depletion at the interface, bestowed dramatically enhanced activity upon the final Pt-support sample, and a smaller Δ Φ means a more effective hydrogen migration. For CoP with the smallest Δ Φ, after Pt loading, the Tafel slope sharply decreased by 3.6 times, meanwhile, the overpotential at 10 mA cm −2 decreased to 53 mV from 242 mV. This work may provide a valuable reference for improving the HER performance through hydrogen spillover.